Locally Advanced Cervical Cancer: Outcomes With Variable Adherence to Treatment. (May 2018) - Manders, Dustin B.; Morón, Abel; McIntire, Donald; Miller, David S.; Richardson, Debra L.; Kehoe, Siobhan M.; Albuquerque, Kevin V.; Lea, Jayanthi S.
Abstract : Objective: Adherence to treatment regimen and schedule is recommended to improve control of disease and overall survival (OS) in locally advanced cervical cancer. However, treatment-related toxicities and patient and physician factors all impact timely completion of treatment. We sought to correlate adherence to treatment plan with survival and toxicities of patients treated for locally advanced cervical cancer. Materials and Methods: A retrospective review of patients treated for advanced cervical cancer at our institution between 2003 and 2011 was performed. Demographics, clinicopathologic variables, treatment, and disease outcomes were collected. Endpoints of disease outcome were disease-free survival and OS. Statistical analyses were performed using the Kaplan-Meier method, log-rank test, and Cox regression analysis. Results: A total of 162 patients met the inclusion criteria and were included in study analysis. A total of 95% of patients were treated with both radiation and concurrent chemotherapy. Mean radiation dose to point A was 72 Gy. In total, 77% had complete response to primary therapy. Severe (grade 3/4) late radiation toxicities were seen in 10.5% of patients. Stage and total radiation dose to point A were significant predictors of survival for the entire cohort. Among patients receiving at least 72 Gy and brachytherapy, duration of treatment was significantly associated with both disease-free survival and OS. Conclusions: Adherence to both optimal treatment time and radiation dose is significantly associated with improved survival. Total radiation dose is an independent predictor of survival among patients with locally advanced cervical cancer.